Limited Sampling Strategy for Estimation of Mycophenolic Acid Exposure in Adult Chinese Heart Transplant Recipients - Xiang, Hongping; Zhou, Hong; Zhang, Jing; Sun, Yongfeng; Wang, Yirong; Han, Yong; Cai, Jie (Frontiers in Pharmacology, 2021)
Background: With the increasing use of mycophenolic acid (MPA) formulations in organ transplantation, the need for personalized immunosuppressive therapy has become well recognized based on therapeutic drug monitoring (TDM) for avoidance of drug-related toxicity while maintaining efficacy. Few studies have assessed area under the 12-hour concentration-time curve of MPA (MPA-AUC0-12h) in heart transplant recipients who received mycophenolate mofetil (MMF) dispersible tablets (MMFdt). The aim of the study was to investigate the pharmacokinetics of MMFdt combined with tacrolimus and further to develop a practical method for estimation of MPA-AUC0-12h using a limited sampling strategy (LSS). Methods: A prospective study in a single center was performed in patients who continuously administrated with MMFdt or MMF capsule (MMFc) for at least 7 days after cardiac transplantation from 2018-2020. A total of 48 Chinese adult heart transplant recipients were enrolled. Blood samples were collected before and 0.5, 1, 1.5, 2, 4, 6, 8, 10 and 12 h after MMF administration. The validated high-performance liquid chromatography combined with tandem mass spectrometry method was used to measure MPA concentrations. Non-compartmental pharmacokinetic (PK) analysis was applied to calculate the data obtained from individual recipients by WinNonlin. LSS models were estimated for MPA-AUC0-12h prediction with multivariate stepwise regression analysis. Results: A large inter-individual variability was observed in AUC0-12h, Tmax, Cmax, MRT0-12h, t1/2 and CL/F after multiple dosing of MMFdt. However, no significant differences were observed between main PK parameters of MMFdt and MMFc. The best estimation of MPA-AUC0-12h was achieved with four points: MPA-AUC0-12h = 8.424+0.781×C0.5+1.263×C2+1.660×C4+3.022×C6 (R2=0.844). The mean prediction error (MPE) and mean absolute prediction error (MAPE) of MPA-AUC0-12h were 2.09±14.05% and 11.17±8.52%, respectively. Both internal and external validations showed good applicability for four-point LSS equation. Conclusion: The results provide strong evidence for the use of LSS model other than a single time-point concentration of MPA when performing TDM. A four-point LSS equation using the concentrations at 0.5, 2 4, 6 h is recommended to estimate MPA-AUC0-12h during early period after transplantation in Chinese adult heart transplant recipients receiving MMFdt or MMFc. However, proper internal and external validations with more patients should be conducted in the future.